2005
DOI: 10.4161/cbt.4.10.1995
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of drug cytotoxicity by iressa (ZD1839) in pancreatic cancer cell lines

Abstract: High expression of the epidermal growth factor receptor (EGFR) family confers a growth advantage on malignant cells in various tumor types. Most pancreatic cancers express EGFR, which seems to play an important role in the acquisition of aggressive clinical behaviour and in tumor invasion. Iressa (ZD1839), a quinazoline tyrosine kinase inhibitor selective for the EGF receptor, has shown good anti-tumor activity in both preclinical and clinical studies. Using two pancreatic cancer cell lines that express differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In head and neck cancer cells as well as xenografts, the combination of gemcitabine followed by gefitinib is superior to the reverse sequence (46). This observation has been supported in pancreatic cancer cells as well where treatment with gemcitabine prior to gefitinib produced additive to synergistic effects but antagonistic effects in response to the reverse sequence (52, 53). This schedule dependent cell killing may be attributable to the cell cycle effects of EGFR inhibitors since EGFR inhibitors upregulate the cyclin dependent kinase inhibitors, p27 (54, 55) and p21 (56) and thus produce G1 cell cycle arrest.…”
Section: Cellular Effects Of Radiation and Gemcitabinementioning
confidence: 78%
“…In head and neck cancer cells as well as xenografts, the combination of gemcitabine followed by gefitinib is superior to the reverse sequence (46). This observation has been supported in pancreatic cancer cells as well where treatment with gemcitabine prior to gefitinib produced additive to synergistic effects but antagonistic effects in response to the reverse sequence (52, 53). This schedule dependent cell killing may be attributable to the cell cycle effects of EGFR inhibitors since EGFR inhibitors upregulate the cyclin dependent kinase inhibitors, p27 (54, 55) and p21 (56) and thus produce G1 cell cycle arrest.…”
Section: Cellular Effects Of Radiation and Gemcitabinementioning
confidence: 78%
“…DNA was extracted from pancreatic cell lines using the QIAmp DNA‐Mini kit (Qiagen, Hilden, Germany), in accordance with the manufacturer's instructions. Exons 18, 19, 20 and 21 of the EGFR gene and exons 5, 6, 7, 8 of the p53 gene were amplified by polymerase chain reaction and DNA sequencing, as previously described (Rengucci et al, 2001; Rosetti et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The synergism of gefitinib with cytotoxics has been tested in vitro on pancreatic cell lines and has showed a differential cytotoxic effect [95,96]. The authors of the study where no response was demonstrated suggested that only EGF receptors with specific mutations are responsive to gefitinib which was not the case in the tested two cell lines used in this study [96].…”
Section: Gefitinibmentioning
confidence: 90%
“…The authors of the study where no response was demonstrated suggested that only EGF receptors with specific mutations are responsive to gefitinib which was not the case in the tested two cell lines used in this study [96].…”
Section: Gefitinibmentioning
confidence: 94%